UJI AKTIVITAS ANTIOKSIDAN KOMBINASI EKSTRAK ETANOL DAUN BELIMBING WULUH (Averrhoa bilimbi L.) DAN DAUN UBI JALAR UNGU (Ipomoea batatas (L.) Lam) DENGAN METODE DPPH (2,2-diphenyl-1-picrylhydrazyl) - hilma hilma (Lembaga Penelitian Sekolah Tinggi Ilmu Farmasi Jl. Kamboja Simpang Baru-Panam, Pekanbaru, Riau 28293 Telp. (0761) 588006, Fax. (0761) 588007 e-mail: editor-jpfi@stifar-riau.ac.id, 2017)
Antioxidant activity of combination ethanol extract of starfruit leaf (Averrhoa bilimbi L.) and purple sweet potato leaf (Ipomoea batatas (L.) Lam) was measured using DPPH (2,2-diphenyl-1-picrylhydrazyl) with vitamin C as comparison . This study aims to determine the best antioxidant activity from the combination of extract of starfruit leaf and purple sweet potato leaf. The extraction was done by maceration method using ethanol solvent. The combination of the two extracts was prepared by comparison (1: 0), (0: ​​1), (1: 1), (1: 2), (2: 1) using ethanol solvent with concentration 50 ppm, 100 ppm, 150 ppm, 200 ppm, 250 ppm and tested its antioxidant activity with DPPH method by Spectrophotometry UV-Vis at 518 nm wavelength to obtain IC50 (Inhibitory Concentration) value. The results showed that IC50 for combination starfruit leaf extract and purple sweet potato leaf with ratio (1: 0), (0: ​​1), (1: 1), (1: 2), (2: 1) were 138.41 ppm, 74.95 ppm, 105.27 ppm, 28.31 ppm, 43.92 ppm and vitamin C is 17.62 ppm. So it can be concluded that the combination of ethanol extract of starfruit leaf (Averrhoa bilimbi L.) and purple sweet potato leaf (Ipomoea batatas (L.) Lam) can increase the antioxidant activity of single extract.